MULTIPLIER EFFECT OF FLOATING NET CAGE BUSINESS ON MANINJAU LAKE TO COMMUNITY ECONOMY IN NAGARI KOTO MALINTANG TANJUNG RAYA DISTRICT AGAM WEST SUMATERA PROVINCE - Siti Erwina Youwikijaya; Hendrik Hendrik; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAK               This research was conducted in April 2017 in Nagari Koto Malintang, Tanjung Raya District, Agam Regency, West Sumatera Province. The purpose of this research is to identify the activity of economic activity which grow as the impact of the existence of floating net cage business and to know the multiplier effect of the existence of floating net cage business (KJA) to the economy of people living around Maninjau Lake Nagari Koto Malintang. The method of this research is quantitative method, informant is determined by Slovin formula and purposive sampling, and data is analyzed by using descriptive analysis and multiplier effect analysis.               The analysis shows that the presence of KJA's business in Kecamatan Tanjung Raya is the base sector and the presence of KJA's business in Nagari Koto Malintang has had an economic impact on the local economy. Direct economic impacts received by business unit owners with a proportion of 3.05 percent, indirect economic impacts received by local workers with a proportion of 4.64 percent and subsequent economic impacts with a proportion of 41 percent. Meanwhile, the Value of Income Multiplier Type II is 2.5. Key Word : Business, Distribution, Investment, Fish Seed, Feasible